Healing Behavior of Simulated Fault Gouges From the Groningen Gas Field and Implications for Induced Fault Reactivation - Hunfeld, Luuk B. (J Geophys Res Solid Earth, 2020)
We investigated the frictional strength recovery (healing) and subsequent reactivation and slip‐weakening behavior of simulated fault gouges derived from key stratigraphic units in the seismogenic Groningen gas field (N. E. Netherlands). Direct‐shear, slide‐hold‐slide (SHS) experiments were performed at in situ conditions of 100 °C, 40 MPa effective normal stress and 10–15 MPa pore fluid pressure (synthetic formation brine). Sheared gouges were allowed to heal for periods up to 100 days before subsequent reshearing. The initial coefficient of (steady) sliding friction μ was highest in the Basal Zechstein caprock (μ = 0.65 ± 0.02) and Slochteren sandstone reservoir (μ = 0.61 ± 0.02) gouges, and the lowest in the Ten Boer claystone at the reservoir top (μ = 0.38 ± 0.01) and in the Carboniferous shale substrate (μ ≈ 0.45). Healing and subsequent reactivation led to a marked increase (∆μ) in (static) friction coefficient of up to ~0.16 in Basal Zechstein and ~0.07 in Slochteren sandstone gouges for the longest hold periods investigated, followed by a sharp strength drop (up to ~25%) and slip‐weakening trajectory. By contrast, the Ten Boer and Carboniferous gouges showed virtually no healing or strength drop. Healing rates in the Basal Zechstein and Slochteren sandstone gouges were significantly affected by the stiffness of different machines used, in line with the Ruina slip law, and with a microphysical model for gouge healing. Our results point to marked stratigraphic variation in healed frictional strength and healing rate of faults in the Groningen system, and high seismogenic potential of healed faults cutting the reservoir and Basal Zechstein caprock units, upon reactivation.